Think Pair Share-Based Learning Module for Global Warming in Grade X Chemistry - Sishy Maharani Putri; Mimi Herman (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Teaching materials play an important role in helping students understand chemistry concepts. However, the teaching materials commonly used in schools are often limited to textbooks, which may not effectively facilitate the learning of abstract concepts such as global warming. This study aimed to develop a Think Pair Share (TPS)-based learning module on global warming for Grade X chemistry students and to evaluate its validity and practicality. The study employed a Research and Development (R&D) approach using the 4-D model, consisting of define, design, develop, and disseminate stages. The research involved one chemistry teacher and 64 Grade X students of SMAN 1 Pariangan. Data were collected through validation sheets and practicality questionnaires and analyzed descriptively using percentage analysis. The results showed that the developed module met the criteria of valid and very valid in terms of content, construct, and language aspects. In addition, the module was categorized as very practical based on both teacher and student responses. These findings indicate that the TPS-based learning module is suitable for use in chemistry learning and can serve as an alternative teaching material to enhance students’ understanding of global warming concepts while promoting active learning.